The Determination Criteria of the Periods of Formation of Students’ Value Orientations at the Institutions of Higher Art Education in Ukraine - Tararak, Nataliya (Pedagogical Discourse, 2013)
The study of students’ value orientations plays a special role in determining the content of psycho- pedagogical support of a young person during the lifetime, including professional development, which is confirmed in the inextinguishable interest of the researchers and practitioners to this issue. A socially significant nature of value orientations prevents the separation of consideration of this phenomenon from the general interests of the society, social and political trends of development in a particular historical period. Periodization as a distribution of historical and pedagogical reality into periods which are qualitatively different from each other is indispensable means of understanding of any historical events and prediction of their possible future development. However, a balanced periodization of value orientations of the art students has never been determined. The objectives of this study are to expose the essence of the creative process in an artistically-pedagogical process, to substantiate and characterize the criteria for period division of the process of forming of the value orientations of students of higher art educational establishments of Ukraine in the ХХ-th century, to define the content, methodology and approaches to this phenomenon investigation on the certain stage of development of higher professional school and scientifically-pedagogical theory on the whole. It was shown that the formation of the students’ value orientations is a complex process that depends on many factors (i.e. an individual’s age characteristics, historical and political conditions , socio-cultural factors, educational content, forms and methods of educational interaction between participants of the educational process at higher school etc.), which are constantly changing. Taken together, the results of the study indicate the relative conditional character of such periodization. Thus, the following criteria have been included into the basis for determining stages of the periodization: – Consideration of the socio-political conditions of the country in the XX century; – Due regard to the social and cultural conditions; – Appeal to the documentary and regulatory base for the development of higher education of this period; – Peculiarities of the theory of the formation of the educational process members’ value orientations; – Content of the higher art education; – Realization of the value pedagogical mutual relations of the participants of the educational process at higher art school. On the basis of the presented methodological grounds to the historical and pedagogical analysis of the national education in its fullness and integrity, continuity and discreteness, against the consideration of the phenomenon of the students’ value orientations in a broad cultural and educational terms as a factor which cannot be productive without solving the current problems of the higher art school in Ukraine, it has been identified three stages of development and formation of value orientations of the educational process participants of the higher art education in Ukraine. They are: the first stage (between 1920 and early 60’s of the XX-th century) – is a phase of creation of the conditions for updating value (axiological ) issues in the national scientific thought against the background of a new type of personality «Soviet student»; the second stage (mid 60ʼs – early 80’s of the XX-th century (1984 ) – is a stage of making perfect the theory and practice of humanistic nature system of value orientations against their reflexive understanding of the inner world of the individual, the third stage (between 1985 and the end of the XX-th century) – is a stage of collapse of the ideological framework of value orientations of the participants in the educational process and at the same time the application of a value- oriented pedagogical mutual relations of a teacher and students in the educational process.